2016
DOI: 10.1136/bcr-2016-216599
|View full text |Cite
|
Sign up to set email alerts
|

Goltz syndrome: a rare case of father-to-daughter transmission

Abstract: An 8-year-old girl presented to us with skin-coloured to yellowish soft compressible papules, intermixed with hypopigmented and hyperpigmented macules in a Blaschkoid pattern, and 'lobster-claw deformity' affecting her bilateral feet. Additional examination findings included short stature, facial asymmetry, low-set ears, hypodontia, enamel hypoplasia, tonsillar enlargement and spina-bifida occulta at S1-3 vertebral level. A diagnosis of Goltz syndrome was suspected clinically, which was confirmed on skin biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although it is usually inherited as an X-linked dominant condition with male lethality in utero, there is a small number of male patients reported in the literature. A possible explanation for this might be due to X-chromosome mosaicism in males that result from gametic half-chromatid mutation or postzygotic somatic mutation [ 4 ]. In reviewing the literature, we found only 6 reports of father-to-daughter transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is usually inherited as an X-linked dominant condition with male lethality in utero, there is a small number of male patients reported in the literature. A possible explanation for this might be due to X-chromosome mosaicism in males that result from gametic half-chromatid mutation or postzygotic somatic mutation [ 4 ]. In reviewing the literature, we found only 6 reports of father-to-daughter transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the literature, we found only 6 reports of father-to-daughter transmission. In all of them, the fathers have been described as having a milder phenotype [ 4 , 5 , 6 , 7 , 8 , 9 ]. In 2016, Prof. Happle [ 10 ] demonstrated that Goltz syndrome represents a developmental defect with mosaic distribution of affected tissues, due to a block of Wnt signal transmission from cells carrying a detrimental PORCN mutation on their active X-chromosome.…”
Section: Discussionmentioning
confidence: 99%